Sodium status and kidney involvement during COVID-19 infection - Post, Adrian (Virus Res, 2020)
The angiotensin-converting enzyme 2 receptor (ACE2) is expressed in epithelial cells of many tissues including the kidney, and has been identified to interact with human pathogenic coronaviruses, including SARS-CoV-2. Although diffuse alveolar damage and acute respiratory failure are the main features of COVID-19 infection, two recent studies demonstrate that kidney impairment in hospitalized COVID-19 patients is common, and that kidney involvement is associated with high risk of in-hospital death. Interestingly, studies in rats have demonstrated that high dietary sodium intake results in down-regulation of the ACE2 expression in kidney tissue. We hypothesize that low sodium status makes kidney involvement during the course of COVID-19 infection more likely due to upregulation of membrane bound ACE2 in the kidneys. We propose that sodium intake and status should be monitored carefully during severe COVID-19 infections, and that low sodium intake be corrected early in its course, despite a potential conflict regarding common dietary recommendations to restrict dietary sodium intake in patients with hypertension, diabetes, and kidney disease.